2018
DOI: 10.1111/bjet.12648
|View full text |Cite
|
Sign up to set email alerts
|

A study of the facilitation of cross‐cultural understanding and intercultural sensitivity using speech‐enabled language translation technology

Abstract: We proposed speech-enabled language translation (SELT) technology that consists of speech-to-text recognition (STR) and computer-aided-translation (CAT) systems to support intercultural communication. When the participants spoke in their native languages, the STR system generated texts from their voice input, and the CAT system translated the STR-generated texts in foreign languages into English. We aimed to investigate whether our approach would be useful to facilitate cross-cultural understanding and the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 18 publications
3
42
0
3
Order By: Relevance
“…Although perfect accuracy of technology is expected, it is difficult to achieve. For example, Huang et al [67], McCrocklin [68], Shadiev et al [9] reported that the accuracy rate of speech recognition is a problematic issue during the learning process. If output generated by recognition systems is not accurate enough, then it is not useful, and is meaningless for learners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although perfect accuracy of technology is expected, it is difficult to achieve. For example, Huang et al [67], McCrocklin [68], Shadiev et al [9] reported that the accuracy rate of speech recognition is a problematic issue during the learning process. If output generated by recognition systems is not accurate enough, then it is not useful, and is meaningless for learners.…”
Section: Discussionmentioning
confidence: 99%
“…With SR support, language learners performed better on comprehension tests than those who did not. SR technology can also be combined with computer-aided-translation technology to support cross-cultural communication [9]. Some problems associated with using SR technology were reported in reviewed articles.…”
Section: Speech Recognition (Sr)mentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the articles according to the above criterions, finally, four studies were selected to be a review related to intercultural learning. In this review, we firstly report and checked selected studies into tables and then reviewed the studies from the following six dimensions: (2) influences of Byram's models on technology used and learning environment, (3) the influences of Byram's models on cultures, languages, different number and level of participants, (4) learning activities and the topics in terms of intercultural learning (5) issues and the solutions, (6) recommendation for the future study and practise.…”
Section: Resultsmentioning
confidence: 99%
“…The rapid advancement of technologies in the last years has created advantages and opportunities for education [2] that the use of technologies has become nearly ubiquitous for foreign/second language (FL/SL) learning. Some new technologies, such as virtual reality, smart watch and other wearable devices are detected and increasingly available [3]. In addition, some emerging technologies, such as Google glasses and computational thinking, are also maturing and very Then, we make a comparison between technologies used from 2014 to 2018 and technologies used before 2014.…”
Section: Introductionmentioning
confidence: 99%